FUNKTIONALITÄTEN DER DISKURSE ZUM WOHNEN DES LOGOS - Pricop, Cosmin (Sacra scripta, 2023)
The present study aims to present different functionalities the theological concept of dwelling or indwelling of the Logos/Jesus Christ gains in some patristic discourses. Regarding Christological functionality the concept of dwelling emphasizes the humanity of Jesus Christ in comparison with his divinity. Within the inner-trinitarian functionality plays the dwelling a role in stressing the cooperation between Father and Son by the incarnation and the presence of Father in Son during his earthly ministry. At the same time, the Holy Spirit resides with the Logos in the human soul of Jesus. For the eschatological functionality the dwelling of Jesus with the saints is presented as the purpose of his return. Finally, the soteriological functionality is illustrated as the reciprocal dwelling between God and man.